L’esaltazione dell’identità nazionale italiana nel discorso di Matteo Renzi - Mamusa, Eleonora (Italianistica Debreceniensis, 2017)
Nations are one of the most well-established constructs in our society, and they represent a very attractive benchmark for personal and social identification. Political speeches, as well as, for example, media discourse and popular culture, constantly reiterate myth, culture and history of nations in order to reaffirm and preserve their positive image, and this tendency doesn’t seem to be weakened by some contemporary events like globalization and the reinforcement of transnational systems. As a proof of this trend, the present work proposes an in-depth analysis of the speech held by the then Italian Prime Minister Matteo Renzi at the European Parliament on the occasion of the inauguration of the Italian semester of presidency on July 2, 2014, aiming to demonstrate that also supranational contexts are exploited to reiterate national identity and priorities.